EFFECT OF DILUTORS ON MOTILITY, MORPHOLOGY AND ACROSOME INTEGRITY OF RAM SPERMATOZOA DURING FREEZING - NEMA, s p; SUTHAR, B N; KAVANl, F S; DHAMl, A J (The Indian Journal of Animal Reproduction, 2023)
The effects of dilutors, rams, stages of freezing process and their interactions were studied in 90 ejaculates in a 3x5x3 factorial experiment for biophysical characteristics of sperms during freezing of sheep semen. The diluents used was 20% egg yolk and 4% glycerol with tris fructose citric acid. (TFCEG), a synthetic phosphate medium (Phos) and sodium citrate glucose egg yolk glycerol (SCGEG). The influences of dilutors, rams, stages of freezing and interactions of dilutor with ram, and dilutorwith stages of freezing were highly significant (P<0.01) on motility and abnormal sperm as well as acrosome score. Maximum post-thaw motility (36.67 ± 1.13%) was observed in TFCEG diluent followed by Phos (31.00 ± 1.43%) and the least in SCGEG (19.83 ± 0.85%) diluent. Rams having better sperm motility at dilution stage could express equally good post-thaw motility in Phos diluent. The percentages of morphologically abnormal sperms and acrosome scores were also significantly (P<0.05) influenced by the dilutors, being minimum in Phos and maximum in TFCEG diluent. Further, the observations indicated that TFCEG provided better protection to sperm motility whereas Phos diluent provided maximum protection to acrosme morphology while cryofreezing of ram semen.